2023
DOI: 10.1002/cam4.5581
|View full text |Cite
|
Sign up to set email alerts
|

Application of EfficientNet‐B0 and GRU‐based deep learning on classifying the colposcopy diagnosis of precancerous cervical lesions

Abstract: Background: Colposcopy is indispensable for the diagnosis of cervical lesions.However, its diagnosis accuracy for high-grade squamous intraepithelial lesion (HSIL) is at about 50%, and the accuracy is largely dependent on the skill and experience of colposcopists. The advancement in computational power made it possible for the application of artificial intelligence (AI) to clinical problems. Here, we explored the feasibility and accuracy of the application of AI on precancerous and cancerous cervical colposcop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Case F has comparable sensitivity to other Experiments. Experiments 1 through 4 have a higher specificity than Case F. Experiment 3 exhibited the highest precision, sensitivity, and specificity levels [33].…”
Section: ) Comparative Analysismentioning
confidence: 87%
See 1 more Smart Citation
“…Case F has comparable sensitivity to other Experiments. Experiments 1 through 4 have a higher specificity than Case F. Experiment 3 exhibited the highest precision, sensitivity, and specificity levels [33].…”
Section: ) Comparative Analysismentioning
confidence: 87%
“…As for the sensitivity Case A has a higher value compared to Experiment 1, experiment 2, and Experiment 4 while Experiment 3 has 0.1082 higher sensitivity compared to Case A, which is 12.38% higher. In terms of specificity, all the experiments, except for experiment 2, have a higher value compared to Case A, while experiments 3 and 4 the perfect specificity and experiment 1 has 2.31% higher compared to Case A [33].…”
Section: ) Comparative Analysismentioning
confidence: 89%
“…Tan et al [32] developed a CNN-based TCT cervical-cancer screening model that improved speed and accuracy and overcame the shortage of medical resources required for cervical cancer screening. One study of colposcopy conducted by Chen et al [33] showed that AI has the potential to assist in colposcopies for the accurate diagnosis of cervical disease and early therapeutic intervention in cervical precancer. Despite the promising performance of AI with colposcopy imaging and TCT, there are still shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…Setting A: Pure CNNs As popular investigating models, E cientNet B0, B4, and B8 models were investigated, with their initial parameters ported from ImageNet-pretrained models [29][30][31][32] . A sigmoid function was used for activation, and binary cross-entropy loss was used to train the NN 33 .…”
Section: Aacm Partmentioning
confidence: 99%